ANALYSIS of Pb, Cu, and Zn CONCENTRATIONS in SEA WATER and SNAILS Cerithidea montagnei from DESA GEMURUH COASTAL WATERS of KUNDUR ISLAND, KARIMUN REGENCY RIAU ISLANDS PROVINCE - Yesi Yohana Esteria; Bintal Amin; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The aim of this research was to find out the relationship between metals Pb, Cu, Zn concentration in sea water and in snail C. montagnei, to determine the pollution level of Desa Gemuruh coastal waters of Kundur Island, as well as to evaluate the safety level of the snail for human consumption. The research was conducted in February – March 2017 by collecting samples from three different stations from Desa Gemuruh coastal waters. Metal concentration analysis was done in Marine Chemistry Laboratory, Faculty of Fisheries and Marine Sciences University of Riau. The results showed that the average Pb, Cu, Zn concentrations in sea waters were 0,0408 mg/L; 0,0438 mg/L; and 0,1424 mg/L, while in snails were 1,0315 μg/g ; 0,9261 μg/g ; 54,1507 μg/g respectively for Pb, Cu, and Zn. The linear regression showed that the raising of Pb and Zn concentration in sea waters, were followed by increasing metal concentrations in snails, but Cu concentration in sea waters were not followed by its increasing concentrations in snails. The larger the body size of the snail the higher metals were accumulated by the snail. This study also showed that MPI values obtain from Desa Gemuruh coastal waters of Kundur Island 3,7260 were classified as lower than other research locations. Snails from this coastal waters are still considered to be safe to be consumed by human with safety level were 6,7864 Kg per week for Pb, 1079,7840 Kg per week for Cu, and 36,1953 Kg per week for Zn.Keywords: Heavy metals, marine pollution, Cerithidea montagnei, Kundur Island